Genotypic differences in agro-physiological, biochemical and isotopic responses to salinity stress in quinoa (Chenopodium quinoa Willd.) plants Prospects for salinity tolerance and yield stability - Hussain, M Iftikhar (Plant physiology and biochemistry : PPB, 2018)
Copyright © 2018 Elsevier Masson SAS. All rights reserved.